Effects of xanthorrhizol on 3T3-L1 adipocyte hyperplasia and hypertrophy - Oon, Seok Fang (2018)
According to the National Health and Morbidity Survey (NHMS) 2015, 47.7% of the Malaysian population are either obese or overweight. The increased obesity prevalence has caused major health problems such as cardiovascular diseases and diabetes. Although several anti-obesity drugs have been developed, they are limited due to adverse side effects such as stroke, myocardial infarction, and depression. These circumstances have increased the demand for effective and safe anti-obesity agents. Previous studies demonstrated that xanthorrhizol (XNT) reduced the levels of serum free fatty acid and triglyceride in vivo, but the detailed anti-obesity activities and its related mechanisms are yet to be reported. In this study, crude oil containing XNT was extracted from Curcuma xanthorrhiza Roxb. by supercritical fluid carbon dioxide extraction. It was further purified by column chromatography and centrifugal thin layer chromatography (TLC). The presence of XNT in each eluate was identified by TLC. The purity of XNT was determined by gas chromatography-mass spectrometry (GC-MS) analysis, whilst its structure was confirmed by proton and carbon nuclear magnetic resonance (NMR) spectral analysis. Next, the IC50 value of XNT was determined by MTT assay. The mode of cell death was further evaluated by annexin V/7-AAD staining for early apoptosis and TUNEL assay for late apoptosis, respectively. The mechanisms involved were determined by quantitative ELISA analysis of caspase-3 and PARP-1 proteins. On the other hand, the ability of XNT to inhibit adipogenesis was examined by oil red O (ORO) staining and glycerol-3-phosphate dehydrogenase (GPDH) activity. The mechanisms involved were evaluated by quantitative ELISA analysis of PPARγ and FAS proteins. The ability of XNT to induce lipolysis was investigated by quantifying the glycerol amount. The mechanisms were examined by quantitative ELISA analysis of leptin and insulin proteins. Statistical significance was analyzed by one-way ANOVA, where p < 0.05 was considered significantly different. Thus, this study aims to evaluate XNT’s abilities to induce apoptosis, impede adipogenesis, and stimulate lipolysis employing 3T3-L1 adipocytes. In this study, XNT purified from centrifugal TLC demonstrated 98.3% purity, and the structure was confirmed by 1H and 13C NMR spectral analysis. The IC50 value of XNT in 3T3-L1 adipocytes was 35 ± 0.24 μg/mL. The loss of cell viability was due to 20.01 ± 2.77% of early apoptosis and 24.13 ± 2.03% of late apoptosis (p < 0.05). XNT elicited apoptosis via up-regulation of caspase-3 and cleaved PARP-1 protein expression for 4.09-fold and 3.12-fold, respectively. Moreover, XNT decreased adipocyte differentiation and GPDH activity in a dose-dependent manner from 3.13 to 12.5 μg/mL. The highest inhibition of adipogenesis was 36.13 ± 3.64% (p < 0.05). The GPDH activity was reduced to 52.26 ± 4.36% by XNT (p < 0.05). It was found that XNT reduced adipocyte formation by impairing the expression of PPARγ to 0.36-fold and FAS to 0.38-fold, respectively. On the other hand, XNT increased glycerol release by 45.37 ± 6.08% compared to control (p < 0.05). During lipolysis, XNT up-regulated the leptin protein for 2.08-fold but down-regulated the protein level of insulin to 0.36-fold (p < 0.05). These results indicated that XNT reduced the volume of adipocytes through modulation of leptin and insulin. To conclude, XNT exerted its anti-obesity mechanisms by suppression of adipocyte hyperplasia through induction of apoptosis (regulation of caspase-3 and PARP-1) and inhibition of adipogenesis (regulation of PPARγ and FAS) whilst reduction of adipocyte hypertrophy through stimulation of lipolysis (regulation of leptin and insulin). Thus, XNT could be developed as a potential anti-obesity agent in the future.